Cartilage organoids and osteoarthritis research: a narrative review - Zeng, Daofu; Chen, Yeping; Liao, Zhidong; Wei, Guizheng; Huang, Xiajie; Liang, Rongyuan; Lu, William W.; Yi, Dan; Chen, Yan (Frontiers in Bioengineering and Biotechnology, 2023)
Osteoarthritis (OA) is one of the most common degenerative joint diseases, significantly impacting individuals and society. With the acceleration of global aging, the incidence of OA is increasing. The pathogenesis of osteoarthritis is not fully understood, and there is no effective way to alleviate the progression of osteoarthritis. Therefore, it is necessary to develop new disease models and seek new treatments for OA. Cartilage organoids are three-dimensional tissue masses that can simulate organ structure and physiological function and play an important role in disease modeling, drug screening, and regenerative medicine. This review will briefly analyze the research progress of OA, focusing on the construction and current development of cartilage organoids, and then describe the application of cartilage organoids in OA modeling, drug screening, and regeneration and repair of cartilage and bone defects. Finally, some challenges and prospects in the development of cartilaginous organoids are discussed.